EXPLORING THE USAGE OF DIGITAL TECHNOLOGIES FOR CONSTRUCTION PROJECT MANAGEMENT - Tung, Yew-Hou; Chia, Fah-Choy; Yong, Felicia Yan-Yan (PLANNING MALAYSIA, 2021)
Digital technologies have recently started to enter the construction industry, gradually changing how infrastructure, real estate and other built assets are designed, constructed, operated and maintained. Being among the least digitalized sectors, it is predicted that digital technologies will substantially increase the productivity, decrease the costs, and improve site safety of construction projects. Thus, the primary objective of this pilot study is to explore the usage of digital technologies for the 12 components of construction project management. A total of 32 respondents participated in the online survey. The results indicate that the usage of digital technologies was significantly higher in the management of scheduling, documenting, designing, and assigning costs. The aspects for digitalized safety, stakeholders, equipment, and materials are room for further improvement.